Factors Affecting Market Entry Mode of Retailer to Enter Developing Country Markets: The Case of Tesco Supermarket - Rattanakomut, Rapeephan (2013)
Intense market competition, market saturation and high rates of globalization have influenced businesses to seek foreign markets for factor endowment, increased sales and sustenance of long-term profits. Developing countries provide foreign markets with high potential owing to increasing incomes, high population and low production costs. This study attempts to apply the Dunning Eclectic Theory on the selection of modes of entry into foreign market in developing countries by Tesco Supermarket. The study collected data from Tesco managers and from company records. The findings indicate that the Eclectic Theory applies to Tesco Supermarket. Ownership advantages of size, international experience influence choice of sole venture entry mode, location advantage of high market potential and high market risks influence sole venture and joint venture respectively, and internalization advantages influence the selection of sole venture. A joint influence of large size, experience in international acquisitions and high market potential is the greatest in driving Tesco to select a sole venture. The study recommends use of size, foreign experience and market potential as primary determinants for selecting an appropriate entry mode into foreign markets in developing countries.